2020
DOI: 10.2478/rjim-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic and clinical characteristics on diabetic painful neuropathy

Abstract: Introduction. Diabetic neuropathy (DN) is one of the most devastating complications of diabetes mellitus; however, in contrast to other countries, there are no scientific studies in Portugal evaluating the impact of demographic and clinical characteristics of this pathological entity. The aim of this study was to evaluate the impact of gender, metabolic control, age of diabetic patients, as well as time of disease progression, the appearance of complaints related to neuropathic pain.Material and methods. A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Thus, it is necessary to exclude other causes not to be confused with pains related to diabetes itself, such as symptoms of spinal lesions, which is a widespread disorder (28). About a quarter of the individuals included in this research had NP, which spotlights the magnitude of this complication and the importance of making health professionals aware of the clinical screening of DPN and NP using specific scales for identifying their signs and symptoms (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to exclude other causes not to be confused with pains related to diabetes itself, such as symptoms of spinal lesions, which is a widespread disorder (28). About a quarter of the individuals included in this research had NP, which spotlights the magnitude of this complication and the importance of making health professionals aware of the clinical screening of DPN and NP using specific scales for identifying their signs and symptoms (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, increased prevalence of pain was related to high levels of Hb1aC, age group, and DM duration. There are no reports associating sex and ethnicity with pain (29,34).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of studies have clearly suggested that men and women respond to pain differently, as well as to pharmacological pain interventions 99 . There was no difference in the prevalence of diabetic neuropathy between different gender, 100 but female may be a risk factor of PDPN 101,102 …”
Section: Sex Differences In Metformin On Painmentioning
confidence: 99%